Relación entre el vínculo materno-fetal y el desarrollo de sintomatología depresiva: una revisión aplicada - Castro Cabrera, Luciana (2023)
Depressive symptoms during pregnancy are a problem that affects many women and can lead to serious disorders such as major or postpartum depression, leading to harmful consequences not only for the mother; but also, for the infant and the family interaction. For this reason, the present investigation sought to identify the relationship between the maternal-fetal bond or prenatal attachment and depressive symptoms. This applied review was carried out following the PRISMA recommendations (Page et al., 2021), in the Web of Science, Scopus and APA PsycNet databases. Ten articles were analyzed, that match with the inclusion and exclusion criteria. The results showed that there are 4 types of relationships between the variables: negative relationship between the general scale of both variables, negative relationship between the subscales of prenatal attachment and depressive symptoms, predictive relationship between both variables, and positive relationship between the subscales of prenatal attachment. and depressive symptoms. It is suggested to continue studying the relationship between both variables due to the need for the results found.